Adsorption of Dyes Using Graphene Oxide-Based Nano-Adsorbent: A Review - Danar Arifka Rahman; Qomarudin Helmy; Mindriany Syafila; Andri Gumilar (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
Graphene Oxide (GO) based adsorbents have attracted much attention from researchers because there have been many reports that they are effective for removing dyes from aqueous environments. That is because GO has good mechanical, electrical, optical and chemical properties, so graphene and its derivatives, such as graphene oxide, have been used in various applications in the field of environmental management. Modifying GO into nano size is an effort to improve its performance in removing dyes. This review uses a database from Science Direct, Google Scholar and Springer, which was screened using graphene oxide, pigments, adsorption and nano adsorbent. The performance of the nano adsorbent showed quite good results in the removal of dyes. The isotherm model suitable for adsorption varies between Langmuir, Freundlich and Redlich-Peterson isotherms. Pseudo-second-order (PSO) is the best model to explain the adsorption process kinetics. Nano-adsorbent modification can be reused at least five times with a reduced adsorption capacity of 4-8%. Studies related to adsorption with GO-based nano adsorbents show promising results in pollutant removal. Still, aspects such as synthesis method, surface functional groups interaction and dye ions and the stability of synthesis products need to be investigated further.